Evidence for reliability, validity and responsiveness of Turkish version of hip outcome score - Polat, Gökhan; Çelik, Derya; Çil, Hilal; Erdil, Mehmet; Aşık, Mehmet (Turkish Association of Orthopaedics and Traumatology, 2017)
Background Hip Outcome Score (HOS), originally developed in English, assesses the severity of hip pathology. To date, no Turkish version of the questionnaire exists. Purpose The aim of our study was to translate the HOS into Turkish and verify its psychometric properties. Methods The translation and cultural adaptation were performed according to international recommendations in five stages: The HOS was translated into Turkish, consistent with published methodological guidelines. The process included 2 forward translations, followed by the synthesis of these translations, and 2 backward translations, followed by an analysis of the translations and creation of the final version. The measurement properties of the Turkish HOS (internal consistency, construct validity, floor and ceiling effects and responsiveness) were tested in 130 patients. Results A committee consisting of the four translators agreed with the final version of the HOS (HOS-Tr). The internal consistency and the test-retest reliability of the HOS-Tr-ADL and HOS-Tr-S subscales were excellent. Correlations between the HOS-Tr and convergent validity of the with HHS and NAHS were fair to good. The responsiveness of the HOS-Tr-ADL and HOS-Tr-S subscales were 3.4 to 1.4 for patients treated with surgically and 0.9 to 1.1 for patients treated with non-surgically. Conclusion The HOS-Tr is understandable, reliably, valid, and responsive for Turkish-speaking patients with hip pathology. Level of Evidence Level 3 Diagnostic Study.
84th IEEE Vehicular Technology Conference, VTC Fall 2016 -- 18 September 2016 through 21 September 2016 -- 126901
Keywords: Clinometric; Hip arthroscopy; Hip Outcome Score; Outcome measurement; Translation; Turkish